The Influence of Celebrity Endorser, Brand Image and Service Quality on Purchase Decision in Tokopedia with Consumer Trust as Intervening Variables - Ratih Ratnasari; Agus Hermawan; Agung Winarno (PT. EQUATOR SINAR AKADEMIA, 2023)
Advantage required consumer trust, service quality, brand image and celebrity endorser to make purchasing decisions for a product. This study aims to determine the direct and indirect influence of celebrity endorsers, brand image and service quality on purchasing decisions at Tokopedia with consumer trust as intervening variables in the city of Surabaya. This study used purposive sampling and snowball sampling techniques with a total of 200 respondents. Data analysis in this study used path analysis using SPSS 22 and Sobel test. The results show that 1) celebrity endorser has a positive and significant effect on consumer trust & purchasing decisions 2) brand image has a significant positive effect on consumer trust and purchasing decisions 3) service quality has a significant positive effect on consumer trust and purchasing decisions 4) consumer trust has a significant positive effect on purchasing decisions 5) celebrity endorser has a significant positive effect on purchasing decisions through consumer trust 6) brand image has a significant positive effect on purchasing decisions through consumer trust 7) service quality has a significant positive effect on purchasing decisions through consumer trust. This study suggests that further research should reach a wider scope.